Modelo ProLab: Vocación 2.0, un aplicativo que ayudará a los jóvenes de quinto de secundaria a escoger su carrera profesional con mayor certeza y seguridad - Ku Sou, Guillermo Dennis (2024)
Vocational indecision is a critical issue that affects most students, leading to dropout rates, career changes, and delays in graduation. This not only limits their personal and professional development opportunities but also causes frustration, low academic performance, and even depression. Addressing vocational indecision as a social issue is urgent and essential to ensure that young people make informed decisions about their future. To tackle this problem, we have developed Vocación 2.0, a comprehensive platform that combines psychological and vocational assessments, detailed information about careers, and comparative charts of universities and degree programs. The platform enables students to explore their interests and abilities, helping them identify the profession that best matches their profile. What makes Vocación 2.0 unique is its integration with advanced generative AI technology. This tool provides personalized recommendations based on the analysis of large volumes of data regarding career paths, job market trends, and individual test results. Also, the AI not only enhances the accuracy of the recommendations but also offers dynamic interactions with students, making the vocational guidance process more efficient and tailored to each individual. Our business model is highly scalable and addresses an unmet need in the educational sector. The platform serves as a bridge between schools and universities, offering cutting- edge technological guidance to support students in making informed decisions. Additionally, we have validated the financial viability of the project, with an NPV of S/.3,463,377.03 and an IRR of 123.89%, ensuring the project’s economic sustainability and its potential for expansion in the educational market.